2019
DOI: 10.21082/littri.v25n1.2019.22-30
|View full text |Cite
|
Sign up to set email alerts
|

PEMANFAATAN LIMBAH KOMODITAS PERKEBUNAN UNTUK PEMBUATAN ASAP CAIR / Utilization of Plantation Commodities Waste for Liquid Smoke

Abstract: Asap cair merupakan hasil kondensasi asap dari proses pirolisis biomassa yang mengandung unsur lignin dan selulosa. Komponen kimia dan fisika asap cair ditentukan oleh bahan baku yang digunakan. Tujuan penelitian ini adalah untuk mengetahui karakteristik asap cair dari limbah komoditas perkebunan yang berbeda. Bahan baku yang digunakan terdiri dari tempurung kelapa, cangkang kelapa sawit dan serbuk gergaji. Tempurung kelapa diperoleh dari pedagang santan di pasar Pangkal Pinang. Cangkang kelapa sawit diambil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Areca nut husk was used as a raw material for liquid smoke, which presented a distinct composition of constituent components compared to wood or shell-based raw materials. Sarwendah et al, 2019;Andy et al, 2021;Darmadji, 1996 demonstrated that raw materials significantly impacted the chemical and physical components of the equipment and the number of compounds generated during the pyrolysis process to produce liquid smoke. Areca nut husk had an average composition of 12.68% moisture, 12.66% hemicellulose, 46.94% cellulose, and 21.21% lignin contents.…”
Section: Betara Variety Of Areca Catechu Husk Analysismentioning
confidence: 99%
“…Areca nut husk was used as a raw material for liquid smoke, which presented a distinct composition of constituent components compared to wood or shell-based raw materials. Sarwendah et al, 2019;Andy et al, 2021;Darmadji, 1996 demonstrated that raw materials significantly impacted the chemical and physical components of the equipment and the number of compounds generated during the pyrolysis process to produce liquid smoke. Areca nut husk had an average composition of 12.68% moisture, 12.66% hemicellulose, 46.94% cellulose, and 21.21% lignin contents.…”
Section: Betara Variety Of Areca Catechu Husk Analysismentioning
confidence: 99%
“…According to Demaji [11], Liquid smoke is a dissolved dispersion of smoke in water, which forms condensation or condensation from steam resulting from pyrolysis of materials which contain lots of lignin, cellulose, hemicellulose and other carbon compounds.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Liquid smoke is an active ingredient that has the ability to inhibit fungal growth obtained from the condensation of vapor or gas fractions formed during the pyrolysis process from materials containing lignin, cellulose and hemicellulose (Sarwendah et al, 2019). Liquid smoke can be used as an antimicrobial because it contains phenolic compounds and organic acids (Pradhana and Trivana, 2018).…”
Section: Introductionmentioning
confidence: 99%